Effect of Feeding Calf Starter Diets Containing Shrimp Waste Meal on Nutrient Utilization in Murrah Buffalo Calves - Aruna, K V N; Srinivas, D Kumar; Rao, E Raghava; Rao, S Jagadeeswara (Indian Journal of Animal Nutrition, 2020)
A 120-day growth trial was conducted using 20 Murrah buffalo calves (Avg. BW 71.0 Â± 1.6 kg) by randomly allotting them to four groups of 5 animals each to study the effect of replacing the protein content of soybean meal with shrimp waste meal at 0, 10, 20 and 30 % levels on nutrient utilization. Chemical composition (% DMB) indicated that shrimp waste meal was rich source of crude protein. Amino acid composition revealed that shrimp waste meal used in the present study is a rich source of serine. Fatty acid composition indicated that shrimp waste meal is rich in saturated fatty acids and also possesses considerable quantities of mono- and poly-unsaturated fatty acids which accounts for 34.86 % of total fatty acids. The digestibility of DM, OM, CP, EE, CF, NFE, NDF, ADF, hemi-cellulose and cellulose increased (P